Retinol oxidation to retinoic acid in human thyroid glandular cells. (December 2014) - Taibi, Gennaro; Gueli, Maria Concetta; Nicotra, Concetta M. A.; Cocciadiferro, Letizia; Carruba, Giuseppe
Abstract Retinoic acid is regarded as the retinol metabolite that controls proliferation and differentiation of epithelial cells. In the present study, we investigated the potential role of xanthine dehydrogenase (XDH) in retinoic acid biosynthesis in human thyroid glandular cells (HTGC). In particular, we observed that cellular retinoids binding proteins (CRBPs) are also implicated in the biosynthetic pathway leading to retinoic acid formation in primary cultures of HTGC, as we have already reported for human mammary epithelial cells (HMEC). After partial protein purification, the enzyme responsible for retinoic acid biosynthesis was identified and quantified as XDH by immunoassay, by its ability to oxidize xanthine to uric acid and its sensitivity to the inhibitory effect of oxypurinol. The evidence of XDH-driven formation of retinoic acid in HTGC cultures further corroborates the potential role of XDH in retinoic acid biosynthesis in the epithelia.